Asymmetric reproductive character displacement in male aggregation behaviour - Pfennig, Karin S. (The Royal Society, 2011)
Reproductive character displacement—the evolution of traits that minimize reproductive interactions between species—can promote striking divergence in male signals or female mate preferences between populations that do and do not occur with heterospecifics. However, reproductive character displacement can affect other aspects of mating behaviour. Indeed, avoidance of heterospecific interactions might contribute to spatial (or temporal) aggregation of conspecifics. We examined this possibility in two species of hybridizing spadefoot toad (genus Spea). We found that in Spea bombifrons sympatric males were more likely than allopatric males to associate with calling males. Moreover, contrary to allopatric males, sympatric S. bombifrons males preferentially associated with conspecific male calls. By contrast, Spea multiplicata showed no differences between sympatry and allopatry in likelihood to associate with calling males. Further, sympatric and allopatric males did not differ in preference for conspecifics. However, allopatric S. multiplicata were more variable than sympatric males in their responses. Thus, in S. multiplicata, character displacement may have refined pre-existing aggregation behaviour. Our results suggest that heterospecific interactions can foster aggregative behaviour that might ultimately contribute to clustering of conspecifics. Such clustering can generate spatial or temporal segregation of reproductive activities among species and ultimately promote reproductive isolation.